2006
DOI: 10.1191/0960327106ht628oa
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac lesions induced by 5-fluorouracil in the rabbit

Abstract: Cardiotoxicity is a rare, but well-recognized complication of treatments with the anti-cancer drug 5-fluorouracil (5FU). The underlying mechanism, however, is not fully elucidated. A spasm of the coronary arteries is often considered to be the leading cause of myocardial ischemia and decreased contractility associated with 5FU. As spasm cannot account for all reported adverse cardiac effects, the present study was undertaken to search for alternative mechanisms. Groups of six rabbits were given either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…A single large dose demonstrated massive hemorrhagic MI associated with coronary spasm, while repeated lower dose infusions resulted in left ventricular hypertrophy with necrosis, thickening of arteries, and apoptosis of endothelial cells. This same study also demonstrated that 5-FU can cause a diffuse myocarditis instead of vasospasm with subendocardial sparing along with inflammation [29]. Another case report utilizing ventricular biopsy demonstrated sarcoplasmic reticulum dilatation, similar to doxorubicin-associated cardiomyopathy [30].…”
Section: Direct Myocardial Injurymentioning
confidence: 72%
See 1 more Smart Citation
“…A single large dose demonstrated massive hemorrhagic MI associated with coronary spasm, while repeated lower dose infusions resulted in left ventricular hypertrophy with necrosis, thickening of arteries, and apoptosis of endothelial cells. This same study also demonstrated that 5-FU can cause a diffuse myocarditis instead of vasospasm with subendocardial sparing along with inflammation [29]. Another case report utilizing ventricular biopsy demonstrated sarcoplasmic reticulum dilatation, similar to doxorubicin-associated cardiomyopathy [30].…”
Section: Direct Myocardial Injurymentioning
confidence: 72%
“…De Forni et al [12] suggested the possibility of a direct drug (or drug-metabolite) toxic action on the myocardium, particularly given evidence that there is global systolic dysfunction, which does not correspond to any individual coronary artery territory. Another animal study demonstrated different toxic effects depending on the dose and frequency of drug administration [29]. A single large dose demonstrated massive hemorrhagic MI associated with coronary spasm, while repeated lower dose infusions resulted in left ventricular hypertrophy with necrosis, thickening of arteries, and apoptosis of endothelial cells.…”
Section: Direct Myocardial Injurymentioning
confidence: 99%
“…Five-fluorouracil gives rise to spasms of the coronary arteries, rhythm disturbance and myocardial and endothelial inflammation underlying their apoptosis at an acute phase of treatment, although at a higher dosage than in the present study. 27 Similarly, a higher dose of cyclophosphamide is toxic for endothelium and myocytes, and causes interstitial hemorrhage and edema. 28 Although the dosage of the present experimental setting did not lead to any severe adverse effects, we need to monitor hemodynamics following treatment of the agents in the clinical setting closely.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 The exact mechanism is currently unclear, but the authors of a systematic review 5 have proposed multifactorial underlying causes, including endothelium-dependent and -independent pathways, direct myocardial damage from cytotoxic effects, induction of apoptosis, rheological side effects, and the production, during drug storage, of cardiotoxic metabolite precursors (for example, fluoro acetate). [6][7][8][9][10][11][12] Animal models of 5-FU cardiotoxicity have manifested apoptosis of myocytes, endothelial cells, or both, which gives rise to clinical presentations similar to that of myocarditis. 12 The toxicity of 5-FU is dependent on the duration of treatment, on the rate of administration, or both; continuous infusions have higher incidences than do bolus regimens.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Animal models of 5-FU cardiotoxicity have manifested apoptosis of myocytes, endothelial cells, or both, which gives rise to clinical presentations similar to that of myocarditis. 12 The toxicity of 5-FU is dependent on the duration of treatment, on the rate of administration, or both; continuous infusions have higher incidences than do bolus regimens. 13,14 Pre-existing cardiac disorders are risk factors for future 5-FU cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%